2002
DOI: 10.1111/j.1745-7599.2002.tb00096.x
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Practice Nurses: A Study of Client Satisfaction

Abstract: Client satisfaction is one indicator used to determine quality of care. Consumer satisfaction benefits the individual client and provides important information for the health care payer. Measuring and reporting client satisfaction with care provided by APNs may increase the visibility and marketability of APNs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 16 publications
0
17
0
4
Order By: Relevance
“…Being treated with respect by health care providers and being involved in treatment decisions are strongly linked to patient satisfaction. 3,6,9,29,37,42 Interestingly, the item ''The registration process is appropriate'' had a much higher correlation to the global measures in the present study than in our previous work 4 (r = 0.693 compared to r = 0.395), while ''My therapist spends enough time'' and ''My therapist listens to my concerns'' was much lower (r = 0.369 compared to r = 0.640, and r = 0.344 compared to r = 0.662, respectively). 4 The reason for this is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Being treated with respect by health care providers and being involved in treatment decisions are strongly linked to patient satisfaction. 3,6,9,29,37,42 Interestingly, the item ''The registration process is appropriate'' had a much higher correlation to the global measures in the present study than in our previous work 4 (r = 0.693 compared to r = 0.395), while ''My therapist spends enough time'' and ''My therapist listens to my concerns'' was much lower (r = 0.369 compared to r = 0.640, and r = 0.344 compared to r = 0.662, respectively). 4 The reason for this is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…These behaviours include respectful deference to others, assurance of human presence, professional skill and knowledge, and attentiveness to others (Wolf et al 1998). In the context of the IMCHB, researchers have reported patients' feelings of being cared for by nurses as important to their satisfaction with care (Russwurm et al 1996, Bear & Bowers 1998, Bryant & Graham 2002.…”
Section: Patients' Personal Elementsmentioning
confidence: 99%
“…In a descriptive study of patient satisfaction with advanced practice nurses, Bryant and Graham (2002) found that affective support, health information received, decisional control, and technical competence all positively influenced overall patient satisfaction with care. Multiple factors and aspects of care within the healthcare arena ultimately determine an individual patient's opinion regarding satisfaction with services rendered.…”
Section: Review Of the Literaturementioning
confidence: 99%